2015
DOI: 10.1016/j.cub.2015.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Visual Responses in the Primate Lateral Geniculate Nucleus

Abstract: The dorsal lateral geniculate nucleus (dLGN) in carnivores and primates is a laminated structure, where each layer gets visual input from only one eye [1, 2]. By contrast, in rodents such as mice and rats, the dLGN is not overtly laminated, the retinal terminals from the two eyes are only partially segregated [3, 4], and many cells in the binocular segment of dLGN get excitatory inputs from both eyes [5, 6]. Here, we show that the evolutionary ancient koniocellular (K) division of primate dLGN, like rodent dLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 41 publications
9
71
0
Order By: Relevance
“…Instead, the high number of components points towards a larger diversity of visual features encoded by dLGN neurons than commonly appreciated, at least in mice. This interpretation is supported by recent studies reporting "non-classical" responses in rodent dLGN [25][26][27][58][59][60] , rabbit dLGN 61 and the koniocellular layers of primate dLGN [62][63][64] , such as direction and orientation selectivity, and binocularity. While our factorization approach reveals an elaborate visual representation at the level of the dLGN, it is still an open question how many distinct types of dLGN neurons exist.…”
Section: Components Of the Dlgn Population Responsesupporting
confidence: 64%
“…Instead, the high number of components points towards a larger diversity of visual features encoded by dLGN neurons than commonly appreciated, at least in mice. This interpretation is supported by recent studies reporting "non-classical" responses in rodent dLGN [25][26][27][58][59][60] , rabbit dLGN 61 and the koniocellular layers of primate dLGN [62][63][64] , such as direction and orientation selectivity, and binocularity. While our factorization approach reveals an elaborate visual representation at the level of the dLGN, it is still an open question how many distinct types of dLGN neurons exist.…”
Section: Components Of the Dlgn Population Responsesupporting
confidence: 64%
“…Considering our results, future studies investigating ocular dominance plasticity and binocular matching will need to disambiguate the relative contributions of thalamic vs. cortical mechanisms for binocular integration. Finally, it will be important to determine whether binocular integration in the primate dLGN (Zeater et al, 2015) is also vulnerable to manipulations during the critical period of development, in order to assess the significance of these findings in the context of amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of recent evidence indicates that significant binocular processing occurs in dLGN in mice (Howarth et al, 2014;Jaepel et al, 2017;Sommeijer et al, 2017) and marmosets (Zeater et al, 2015). A retrograde tracing study (Rompani et al, 2017) demonstrated that single dLGN neurons receive direct retinal inputs from both eyes, providing an anatomical substrate for binocular integration in the mouse dLGN.…”
Section: Introductionmentioning
confidence: 99%
“…2 (ii) There are additional local maxima at other disparities (false matches). (iii) The response map is much smoother than the pixelation of the original image (reducing the number of false matches), which simply reflects the fact that the monocular RFs pool over a finite spatial extent.…”
Section: The Binocular Energy Model and The Stereo Correspondence Promentioning
confidence: 99%